Strangers an pilgrims, travellers and sojourners: Leiden and the Foundations of Plymouth Plantation - Bangs, Jeremy Dupertuis (General Society of Mayflower Descendants, 2009)
"Controversies in politics and religion, customs of family life and society, obligations of labor and chances to play, questions of free will, democracy, the separation of church and state, religious toleration, treatment of Indians---these form the matter of this book." -- Publisher's description